Importance for implementationof spatial planningas an integrated land management tool in Ukraine - Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2017)
Scientific publications, legislation on spatial planning in Ukraine and spatial planning in Austria are analysed. Ukrainian spatial planning system is divided into urban planning and land management planning.Urban development field belongs lion’s share of planning tools, while in Ukraine is only about 4% of the land is built-up. Comprehensive conceptual spatial planning is inherently absent in Ukraine. Only single brancheshave tools for conceptual planning on the nationallevel, and therefore planning effectiveness is negligible. The existing system in Ukraine is in its essence the legacy of Soviet planning system, the aim of which was to establish production processes and the use of everything that can be used for economic purposes. Also, it can’t effectively respond to modern trends in social and economic spheres. The lack of conceptual planning system also leads to inconsistent planning actions between different sectors, making it impossible to fully realize the ideas of actors from different spheres. Another obstacle is the lack of real long-term impact tools (approved at the state level planning and forecasting documents). So on a practical level, most of the decisions are more situational and not promising. Austria’ssystem of spatial planninghas tools which provide conceptual planning at the federal level. Every decade Austrian Conference on Spatial Planning (ÖROK)is convened. The conference develops and approvesAustrian Spatial Development Concept for 10 years (ÖREK).This concept is not a directly applicable law and does not require its implementation, but its implementation is achieved by the fact that it’s developed in cooperation of the entire country and everyone feels responsibility for compliance and implementation of these ideas. By comparing approaches to spatial planning in Austria and spatial planning in Ukraine, it’s found that the planning system of Ukraine requires conceptual changes. It is important to create a collective body under the Cabinet of Ministers, which would develop the concept of spatial development of Ukraine. The Law of Ukraine "On the general scheme of planning the territory of Ukraine" should be amended to make this toolnot narrow specialized but general, comprehensive and the one which put a human in its centre. It is also necessary to amend the Law of Ukraine "On Land Management" and "On regulation of urban development" to systematize planning tools. It is important that the concept of "spatial planning" would be regulated by these laws and would becomea new meaning. Keywords: land use planning, spatial planning, territorial planning.